Perancangan Modul dan Video Pelatihan terkait Gaya Kepemimpinan Supervisor di PT. X - Ronan Yadi Sunarto; I Nyoman Sutapa (Jurnal Titra, 2022)
Awareness of the various leadership styles will help people to work more effectively by understanding how and why they do what they do, as well as helping them identify where and when they need to adjust their style, especially for supervisors at PT. X. This is because they are in charge of leading and maintaining a department. PT. X is a company engaged in the production of medicines. The company then wants to design training with the help of training modules and videos to increase the effectiveness and efficiency of the training. The analysis was conducted to determine the most dominant leadership style supervisors possess at PT. X is done in two ways, namely analysis based on field observations and analysis based on the theory of Peter G. Northouse. The results of the two analyses indicate the most dominant leadership style possessed by supervisors at PT. X is democratic leadership. The design of training modules and videos considers the criteria for the correct training modules and videos and has been validated by the company.